Effect of MgSO4 Administration on The Incidence of Acute Kidney Injury and Renal Function in Lung Cancer Patients Receiving Cisplatin Chemotherapy - Lestari, Nastiti; Setiadji, Ana Rima; Suseno, Aryo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Platinum-based chemotherapy is the most common lung cancer therapy currently performed with satisfactory results, but the use of platinum-based chemotherapy, such as cisplatin, can cause cisplatin-induced nephrotoxicity (CIN). MgSO4 is a substance that has been studied and is known to have a protective effect on the kidneys. This study aims to determine the effect of MgSO4 administration on the incidence of CIN in lung cancer chemotherapy patients receiving cisplatin chemotherapy. Methods: This was a quasi-experimental study with a pre-test and post-test control group design. The study group received intravenous MgSO4 20 mEq, and the control group received standard therapy without MgSO4. The incidence of CIN was assessed based on the incidence of acute kidney injury (AKI) and renal function measured by the estimated glomerulus filtration rate (eGFR). Results: The incidence of AKI in the treatment group was 6.67%, whereas the control group had no incidence of AKI (P=0.32). Renal function (eGFR) showed no significant difference between the treatment and control groups (P=0.86), although both groups exhibited improved renal function post-chemotherapy. Conclusion: MgSO4 administration does not affect the incidence of AKI and renal function of lung cancer patients receiving cisplatin chemotherapy.